Pertanggungjawaban Pidana Pelaku Tindak Pidana Penganiayaan yang Direncanakan (Studi Kasus Putusan Pengadilan Negeri Bangli Nomor 19/pidB/2019/PNBLI) - I Dewa Gede Windhu Indrakusuma (Jurnal Preferensi Hukum, 2021)
Maltreatment is an act that causes injury or pain to someone which is done on purpose. The maltreatment consisted of light maltreatment and severe torture. This study aims to determine the criminal sanctions against the planned perpetrators of maltreatment and to analyze the considerations of the judge's decision against the perpetrators of the planned maltreatment. This type of research is normative legal research using a statutory approach. The technique of collecting legal materials is done by interviewing techniques. The results of the study show that the criminal sanction against the perpetrator of the planned maltreatment is a maximum of four years in prison as regulated in Article 353 paragraph 1 of the Criminal Code, while in the case of decision Number 19 / pidB / 2019 / PNBLI, the perpetrator I Made Merta is subject to imprisonment for four months according to Article 353 paragraph 1 of the Criminal Code where the elements contained therein are all fulfilled. Then, the judges' considerations in the perpetrators of the planned maltreatment included considerations of a juridical nature, namely things that were burdensome and things that were mitigating, whereas in the case study decision Number 19 / pidB / 2019 / PNBLI the judge considered more about the history of the defendant, namely the defendant. polite and admit that his actions in court have never been convicted and there has been peace between witnesses victim I Gede Jasa, so the judge sentenced Article 353 of the Criminal Code, which is four (4) months.